2006
DOI: 10.1097/01.mnm.0000237987.31597.cf
|View full text |Cite
|
Sign up to set email alerts
|

A method for quantitative cell tracking using SPECT for the evaluation of myocardial stem cell therapy

Abstract: In dual-isotope SPECT, corrections for physical effects were required to detect transgene expression in cells transplanted into an infarction when localization information was available.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
16
0

Year Published

2007
2007
2015
2015

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 28 publications
0
16
0
Order By: Relevance
“…By labeling canine bone marrow mesenchymal cells with 111 In-tropolone, we have estimated the limit of detection at 3,200 cells, with a radioactive burden of 0.14 Bq per cell (20). Additionally, our group has also shown that application of corrections for Compton scatter, radionuclide crosstalk, and attenuation in SPECT image processing can improve multiisotope detection (11). Therefore, we have shown that multiisotope SPECT can be very sensitive and quantitative.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…By labeling canine bone marrow mesenchymal cells with 111 In-tropolone, we have estimated the limit of detection at 3,200 cells, with a radioactive burden of 0.14 Bq per cell (20). Additionally, our group has also shown that application of corrections for Compton scatter, radionuclide crosstalk, and attenuation in SPECT image processing can improve multiisotope detection (11). Therefore, we have shown that multiisotope SPECT can be very sensitive and quantitative.…”
Section: Discussionmentioning
confidence: 96%
“…Recently, our group has developed a method to use multiisotope SPECT for detection of gene expression, cell location, and perfusion to assess the effects of stem cell therapy in a large animal model of myocardial infarct (11). In dogs harboring bone marrow-derived mesenchymal cells expressing HSV1-TK, they were able to simultaneously detect gene expression with 131 I-FIAU, verify the location of the stem cell transplants with 111 In, and assess the effects of stem cell transplantation on myocardial perfusion with 99m Tc-sestamibi (11).…”
mentioning
confidence: 99%
“…In addition, radiolabeled oligonucleotide can bind an mRNA transcript and radiolabeled antibodies/antibody-like structures can target cell-surface proteins [76]. Radioactive atoms, including 99mTc and 111In have been commonly used for labeling pre-transplant cells such as MSCs and proven effective without affecting the viability and differentiation capacity of the MSCs [75,79,80]. In addition, dual labeling has been performed.…”
Section: Nuclear Imagingmentioning
confidence: 99%
“…PET detects two anti-parallel 511-keV gamma rays and it has a higher sensitivity than SPECT, and thus, more accurate in quantification analysis. Methods for stem cell labeling involves direct loading with a radiometal [73][74][75] and indirect labeling through enzymatic conversion and retention of a radioactive materials or receptor mediated binding [74,76,77].…”
Section: Nuclear Imagingmentioning
confidence: 99%
“…This includes the lack of immunogenicity of the human NIS transgene and the fact that SPECT scanning of radiotracers such as 99m Tc and 123 I is widely available at relatively low cost and is approved by responsible regulatory authorities such as the Food and Drug Administration. Moreover, recent progress in quantification of tracer signals with the use of clinical SPECT systems 21 emphasizes the potential of this approach for tracking cellular transplants in large animals and patients. To date, however, the strategy was evaluated only in a small-animal model focused on detection of acute cell retention after administration of cardiac derived stem cells.…”
Section: Editorial See P 388 Clinical Perspective On P 439mentioning
confidence: 99%